PROBLEMS IN DETERMINING THE ACTUAL PROPERTY BOUNDARIES !COORDINATES" IN THE COURSE OF FORENSIC LAND SURVEY - V. Tishkin; E. Seregina; R. Kazyulin; G. Omelyanyuk (Теория и практика судебной экспертизы)
The paper presents the key problems concerning the geodesic description of propertylocation with the help of turning point coordinates of its boundaries in the establishedsystem of coordinates. It examines the advantages of incorporating innovative globalpositioning technologies into forensic land survey procedures.